A novel stop-gain mutation in ARMC2 is associated with multiple morphological abnormalities of the sperm flagella. Issue 5 (November 2021) - Khan, Ihsan; Dil, Sobia; Zhang, Huan; Zhang, Beibei; Khan, Teka; Zeb, Aurang; Zhou, Jianteng; Nawaz, Shoaib; Zubair, Muhammad; Khan, Khalid; Ma, Hui; Shi, Qinghua
Abstract: Research question: Male infertility is a global issue worldwide and multiple morphological abnormalities of the sperm flagella (MMAF) is one of the most severe forms of the qualitative sperm defects with a heterogeneous genetic cause that has not been completely understood. Can whole-exome sequencing (WES) reveal novel genetic causes contributing to MMAF in a consanguineous Pakistani family, comprising three infertile brothers? Design: WES and bioinformatic analysis were conducted to screen potential pathogenic variants. The identified variant was validated by Sanger sequencing in all available family members Transmission electron microscopy analyses was carried out to examine the flagella ultrastructure of spermatozoa from patient. Results: WES and Sanger sequencing identified a novel homozygous stop-gain mutation (ENST00000392644.4, c.182C>G, p.S61X) in ARMC2, which is expected to lead to loss of protein functions. Transmission electron microscopy analyses revealed that the flagellar ultrastructure of the patient's spermatozoa was disorganized along with a complete absence of central pair complex (CPC), suggesting that ARMC2 is involved in the assembly, stability of the axonemal complex, or both, particularly the CPC. Conclusion: We report that a familial stop-gain mutation in ARMC2 is associated with male infertility in humans caused by MMAF accompanied with loss of CPCs and axonemal disorganization. We provide genetic evidence that ARMC2 is essential for human spermatogenesis and its mutation may be pathogenic for MMAF. These findings will improve the knowledge about the genetic basis of MMAF and provide information for genetic counselling of this disease. Graphical abstract: Image, graphical abstract